Residual efficacy of selected larvicides against Culex pipiens pipiens (Diptera: Culicidae) under laboratory and semi-field conditions - Maria K. Sakka; Charalampos S. Ioannou; Nikos T. Papadopoulos; Christos G. Athanassiou (Environmental Science and Pollution Research, 2023)
Mosquitoes are a threat worldwide since they are vectors of important pathogens and parasites such as malaria, dengue, yellow fever, and West Nile. The residual toxicity of several commercial mosquito larvicides was evaluated for the control of Culex pipiens pipiens under controlled laboratory and semi-field conditions during late spring and summer of 2013. The evaluation included six different active ingredient formulations, i.e., diflubenzuron Du-Dim), Bacillus thuringiensis var. israelensis ( Bti ) (Vectobac), spinosad (Mozkill), S-methoprene (Biopren), temephos (Abate), and polydimethylsiloxane (PDMS) (Aquatain), that are currently registered of and had been registered in the past for mosquito control. Under controlled laboratory conditions, the residual activity ranged from 1 week (S-methoprene) up to 2 months (spinosad, PDMS). Exposure of larvicides under semi-field conditions resulted in noticeable differences regarding their efficacy as compared to the laboratory bioassays. Exposure of S-methoprene, Bti , and spinosad, for up to 3 days, resulted in similar adult emergence to the controls. On the other hand, the residual efficacy of diflubenzuron, temephos, and PDMS ranged from 14 to 28 days, depending on the season of exposure. Longevity and fecundity of adults that had emerged from surviving larvae, in most of the cases tested, did not differ significantly from that of the controls. The results of the present study demonstrate the necessity of both field and laboratory studies to draw safe conclusions regarding the efficacy of larvicides against mosquitoes and the selection of the proper formulation for each application scenario. In addition, defining the seasonal variation in the residual toxicity of the tested formulations could be useful for improving mosquitos’ management programs.